Implementation of Three End's Program in Improving Women's Protection - Aprilia Pratiwi; Ahmad Riyadh (Indonesian Journal of Law and Economics Review, 2022)
This study aims to describe and analyze the implementation of the Three End's program in increasing the protection of women as well as the supporting and inhibiting factors in the implementation of the Three End's program in Sidoarjo Regency. This research is a descriptive qualitative research using a purposive sampling technique in determining the informants. The informants in this study were the Head of the Section for the Protection of Women's Rights and Special Protection for Children (DP3AKB), the Head of the Division of Women's Empowerment and Child Protection (DP3AKB), the Head of the Administration Section (UPTD PPA), the Personnel Manager (DP3AKB), and the Sidokepung Village Community. Techniques for collecting data are through interviews, observations and documentation. The data analysis technique uses an interactive analysis model consisting of data collection, data reduction, data presentation and conclusion drawing. The results of the research on the implementation of the Three End's program in improving women's protection are communication indicators consisting of the transmission dimension, which is right on target, the clarity dimension to get clear information can directly ask the local village government, the consistency dimension in complaints of violence is in the UPTD PPA. Disposition, the dimension of bureaucratic appointment is the authority of the BKD and the dimension of incentives as employee motivation at work. In this study, the researchers took a research place at DP3AKB Sidoarjo Regency.